2009
DOI: 10.1016/j.peptides.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing hypothalamic ghrelin receptor gene expression on energy balance

Abstract: Central and peripheral injections of Ghrelin potently stimulates food intake via its receptor, GHSR1a expressed in the brain. In this study, we explored the role of GHSR1a in the paraventricular nucleus of the hypothalamus (PVN) by reducing their gene expression using the RNA interference (RNAi). pSUPER plasmids inserted with sh (short hairpin)-GHSR1a were injected into the PVN to reduce its expression. The transfected rats were monitored daily for their food intake and body weight throughout the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Collectively, these observations support that ghrelin is not a regulator of food intake in rodents in standard housing conditions. In contrast, our results emphasized the role of ghrelin in fat storage, which is in agreement with previous observations supporting that both adipogenic and orexigenic roles of ghrelin are independently regulated (8,44). On the other hand, our observations are consistent with those in Ghsr -/-mice supporting that ghrelin-GHSR signal is not a key contributor to somatic growth in rodents (10).…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, these observations support that ghrelin is not a regulator of food intake in rodents in standard housing conditions. In contrast, our results emphasized the role of ghrelin in fat storage, which is in agreement with previous observations supporting that both adipogenic and orexigenic roles of ghrelin are independently regulated (8,44). On the other hand, our observations are consistent with those in Ghsr -/-mice supporting that ghrelin-GHSR signal is not a key contributor to somatic growth in rodents (10).…”
Section: Discussionsupporting
confidence: 93%
“…5B). A previous study demonstrated that knockdown of GHSR mRNA in this nuclei reduces body weight and blood ghrelin levels without affecting food intake (35). This suggests a divergence between energy intake and body weight and may provide a mechanism by which DIO mice maintain obesity in the absence of excess caloric intake.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies examined the role of ghrelin in the PVN by selectively knocking down GHSRs in vivo (60% knockdown) using RNA interference. GHSR knockdown does not affect daily food intake but significantly reduces body weight and blood ghrelin levels [61]. Thus, direct ghrelin activation of GHSR in the PVN regulates body weight independently of food intake.…”
Section: Ghrelin Mediates Food Intake and Body Weight Independentlymentioning
confidence: 99%